Reliability-based design: Artificial neural networks and double-loop reliability-based optimization approaches. (March 2018) - Lehký, D.; Slowik, O.; Novák, D.
Highlights: Two approaches for solving a reliability-based design problem are proposed. Artificial neural network based inverse reliability method has been implemented. Double-loop reliability-based optimization method has been implemented. Verification using examples of structural design was carried out. Abstract: Two advanced optimization approaches to solving a reliability-based design problem are presented. The first approach is based on the utilization of an artificial neural network and a small-sample simulation technique. The second approach considers an inverse reliability task as a reliability-based optimization task using a double-loop optimization method based on small-sample simulation. Both techniques utilize Latin hypercube sampling with correlation control. The efficiency of both approaches is tested using three numerical examples of structural design – a cantilever beam, a reinforced concrete slab and a post-tensioned composite bridge. The advantages and disadvantages of the approaches are discussed.